1973
DOI: 10.1111/j.1476-5381.1973.tb08348.x
|View full text |Cite
|
Sign up to set email alerts
|

On the pharmacology of ascending, descending and recurrent postsynatic inhibition of the cuneo‐thalamic relay cells in the cat

Abstract: Summary1. In cats decerebrated or anaesthetized with pentobarbitone, cells of the middle third of the cuneate nucleus that were excited by tactile stimulation of the ipsilateral forelimb (responding to displacement of hairs, skin or joints) and inhibited by electrical stimulation of the contralateral pyramid, were invariably inhibited by electrical stimulation of the ipsilateral forepaw and the contralateral forelimb nerves. 2. In 50% of the cats, the cells were more fully identified by placing electrodes ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…8 A, Control). This presumed recurrent suppression (Kelly and Renaud, 1973;Canedo et al, 2000) was observed at stimulating frequencies of up to 20 -25 Hz and was canceled by application of BiCu (Fig. 8 A, right) and/or strychnine.…”
Section: Effects Of Microiontophoresed Gaba And/or Glycinementioning
confidence: 99%
“…8 A, Control). This presumed recurrent suppression (Kelly and Renaud, 1973;Canedo et al, 2000) was observed at stimulating frequencies of up to 20 -25 Hz and was canceled by application of BiCu (Fig. 8 A, right) and/or strychnine.…”
Section: Effects Of Microiontophoresed Gaba And/or Glycinementioning
confidence: 99%
“…An alternative explanation could involve the possibly different distributions of GABA receptors at pre-and post-synaptic sites in cuneate nucleus and cerebral cortex. Both pre-and post-synaptic inhibition have been demonstrated in the cuneate nucleus (Andersen, Etholm & Gordon, 1970) and GABA has been suggested as the transmitter for both mechanisms (Banna & Jabbur, 1969;Davidson & Reisine, 1971;Kelly & Renaud, 1971;Banna, Naccache & Jabbur, 1972;Kelly & Renaud, 1973c). In the cortex, however, only a post-synaptic action of GABA has been shown to occur, as yet (Krnjevic & Schwartz, 1968).…”
Section: Experimentalproceduresmentioning
confidence: 99%
“…Similar degrees of block occurred whether the cells were excited postsynaptically by glutamate or transynaptically by peripheral stimulation of hair, touch or joint cells. In the second paper (Kelly & Renaud, 1973a) glycine is shown to be selectively blocked by extremely small and short iontophoretic applications of strychnine. The third paper (Kelly & Renaud, 1973b) describes the influence of bicuculline, picrotoxin and strychnine on the duration and intensity of inhibition of cuneothalamic relay cells.…”
Section: Introductionmentioning
confidence: 99%